Negative Impact of the COVID-19 Pandemic on Admissions for Intracranial Hemorrhage - Abdulazim, Amr; Ebert, Anne; Etminan, Nima; Szabo, Kristina; Alonso, Angelika (Frontiers in Neurology, 2020)
Background. The COVID-19 pandemic has seriously impacted healthcare systems worldwide. Admissions for various non-COVID-19 emergencies have significantly decreased. We sought to determine the impact of COVID-19 on admissions for intracranial hemorrhage to a German University Hospital emergency department. Methods. In a retrospective analysis of admissions to the emergency department of the University Hospital Mannheim from January to June 2020 and the corresponding time period in 2019, all patients admitted for either traumatic or non-traumatic intracranial hemorrhage were evaluated. Poisson regression was performed to analyze changes in admission rates as a function of year, epoch (COVID-19-epoch, March to April 2020 and corresponding months 2019; non-COVID-19-epoch, January to February and May to June 2019/2020) and the interaction of year and epoch (reflecting the impact of the pandemic and subsequent lockdown measures). Results. Overall, 320 patients were included in the study. During the COVID-19-epoch, admission rates for spontaneous intracranial hemorrhage decreased significantly by 42.1% (RR 0.579, p = 0.002, 95% confidence interval 0.410-0.818). Likewise, admission rates for traumatic intracranial hemorrhage decreased significantly by 53.7%, (RR = 0.463, p < 0.001, 95% confidence interval (CI) 0.358-0.599). Conclusion. The decrease of spontaneous intracranial hemorrhages may be a consequence of underutilization of the healthcare system whereas decreasing rates of traumatic intracranial hemorrhage admissions may predominantly reflect a decrease in true incidence rates due to lockdown measures with restricted mobility. Raising patient awareness to seek emergency healthcare for acute neurological deficits during lockdown measures is important to ensure appropriate emergency care for patients with intracranial hemorrhage.